Trajectories of psychosocial working conditions and all-cause and cause-specific mortality: a Swedish register-based cohort study - Pan, Kuan-Yu; Almroth, Melody; Nevriana, Alicia; Hemmingsson, Tomas; Kjellberg, Katarina; Falkstedt, Daniel (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVES ': 'While psychosocial working conditions have been associated with morbidity, their associations with mortality, especially cause-specific mortality, have been less studied. Additionally, few studies considered the time-varying aspect of exposures. We aimed to examine trajectories of job demand–control status in relation to all-cause and cause-specific mortality, including cardiovascular diseases (CVD), suicide, and alcohol-related mortality. ' ' METHODS ': 'The study population consisted of around 4.5 million individuals aged 16-60 years in Sweden in 2005. Job control and demands were respectively measured using job exposure matrices (JEM). Trajectories of job control and demands throughout 2005–2009 were identified using group-based trajectory modelling, and job demand–control categories were subsequently classified. Deaths in 2010–2019 were recorded in the national cause of death register. Cox regression models were used. ' ' RESULTS ': 'A total of 116 242 individuals died in 2010–2019. For both job control and demands, we identified four trajectories, which were parallel to each other and represented four levels of exposures. Low control and passive jobs were associated with higher all-cause, CVD, and suicide mortality among both men and women. High strain jobs were associated with higher all-cause and CVD mortality among men, while low control, passive jobs, and high strain jobs were associated with higher alcohol-related mortality among women. ' ' CONCLUSIONS ': 'The trajectories identified may suggest stable levels of job control and demands over time. Poor psychosocial working conditions are related to all-cause and cause-specific mortality, and these patterns vary to some extent between men and women.
Keywords: alcohol-related; all-cause mortality; cardiovascular disease; cause-specific mortality; death; group-based trajectory modelling; job control; job demand; job demand-control; psychosocial; psychosocial working condition; register-based cohort study; suicide; Sweden; trajectory